Important aspects of teaching physics in relation to the Social Sciences - Raximberdieva Dilrabo (Genius Journals, 2025)
This article explores the integration of physics teaching with social sciences, emphasizing the importance of interdisciplinary approaches in education. It analyzes existing literature, outlines effective teaching methods, and presents the results of implementing interdisciplinary techniques in classroom settings. The discussion highlights the benefits and challenges of such an approach, concluding with practical suggestions for educators.
Keywords: Physics education; social sciences; interdisciplinary teaching